Impact of gamification on GenZ consumers' online impulse buying behavior intention: evidence from Shopee application in the Vietnamese market - Tran Thanh Tu; Nguyen Thi Hai Binh (Proceedings The International Conference on Business Based on Digital Platform (BDP-3), 2023)
In the ever-evolving realm of electronic commerce, the volatility of customer buying patterns, specifically impulsive purchases, has escalated. The objective of this study is to examine the integration of gamification strategies within online shopping applications, with the aim of enhancing user satisfaction and stimulating impulsive buying behavior in the online context. This study utilizes the Theory of Mind (ToM) and Stimulus-Organism-Response (SOR) framework in conjunction with Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the influence of gamification elements on impulsive buying behavior, as observed through individual cognitive reactions. By employing a judgemental sampling technique, the study successfully gathers 204 data points via an online survey. Subsequent data analysis confirms the validity of six out of the eight hypotheses, indicating that the impact of random rewards on impulsive purchasing is constrained. This highlights the necessity for e-commerce platform administrators to enhance their gamification strategies, while also indicating that Generation Z (GenZ) consumers might modify their buying behaviors accordingly.
Keywords: 330; gamification; Gen Z; impulsive buying; SOR framework